1995
DOI: 10.3109/00016349509008919
|View full text |Cite
|
Sign up to set email alerts
|

Paracervical Block‐A Viable Alternative for Labor Pain Relief?

Abstract: PCB in selected parturients with a low-dose superficial technique has been shown to be an effective analgesic modality with minimal fetal and neonatal side-effects, but post-blockade fetal bradycardia cannot be wholly eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…In our study, the mean VAS score 30 min after PCB was 4.3; in other studies values between 4.6 and 5.0 have been found (8–10). Although in many cases some pain remained after PCB, the block did not negatively affect the progress of labor, in contrast to the situation concerning epidural analgesia, which has been found to be associated with longer labor and a higher rate of instrumental vaginal delivery (11).…”
Section: Discussionsupporting
confidence: 55%
“…In our study, the mean VAS score 30 min after PCB was 4.3; in other studies values between 4.6 and 5.0 have been found (8–10). Although in many cases some pain remained after PCB, the block did not negatively affect the progress of labor, in contrast to the situation concerning epidural analgesia, which has been found to be associated with longer labor and a higher rate of instrumental vaginal delivery (11).…”
Section: Discussionsupporting
confidence: 55%
“…Heart rate changes, bradycardia in particular, have been reported to occur in up to 70% of fetuses after PCB ( 1, 2). However, modifications of the early method of PCB by decreasing the dose and concentration of the local anesthetic and by using superficial injection technique have significantly reduced the incidence of PCB‐induced fetal bradycardia to the range of 2–10% ( 3–6). Epidural analgesia, though generally considered safe, often decreases maternal blood pressure, with potentially harmful fetal effects ( 2, 7, 8).…”
mentioning
confidence: 99%
“…8 In this study the low rate of FHR abnormalities after PCB was similar to other studies, which have reported bradycardia rates of 0-12% and mostly 2% or lower. 3,[7][8][9]13,14,18 According to published literature the risk of fetal bradycardia is increased when intrathecal opioids are used as part of a regional analgesia technique. It is suggested to be related to the fast onset of analgesia, rapid decrease of maternal circulating b-adrenergic agonists, intense uterine contractions and decreased uteroplacental blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, when administered by lowdose superficial injection by an experienced obstetrician, PCB has been found to be safe. [3][4][5][6][7][8][9] Conversely studies of spinal opioids have reported increased fetal bradycardia rates, and the value of spinal analgesia with opioids has therefore been questioned. 10 In Finland and in our delivery unit PCB and singleshot spinal (SSS) analgesia are widely used.…”
Section: Introductionmentioning
confidence: 97%